Prosodic change and majority language influence in spoken North Sámi varieties - Hiovain-Asikainen, Katri (Helsingin yliopisto, 2023)
This dissertation investigates acoustic and prosodic features of North Sámi, a Uralic minority language traditionally spoken across northern Norway, Sweden, and Finland. The focus is on spoken variations within specific regions, influenced by majority languages. The study diverges from traditional dialectal analysis by examining varieties according to state borders. It comprises four publications ([P1] to [P4]) using multidisciplinary methods to explore prosodic characteristics and change in spoken North Sámi. [P2] and [P3] delve into word and phrase-level phenomena using modern language and speech technology methods. [P1] and [P4] study specific prosodic aspects of ternary quantity in North Sámi via more traditional acoustic phonetic analysis. [P2] identifies a positive correlation between geographical and prosodic distances among five North Sámi varieties from Norway and Finland. Close geographic proximity aligns with similar prosodic features. Mutual cross-entropy clustering groups varieties by majority language/country rather than traditional dialectal distinctions. [P3] uncovers varied prosodic manifestations of verbs and nouns in North Sámi varieties spoken in Norway and Finland. Norwegian North Sámi speakers employ f0 peaks to mark words prosodically, resembling Norwegian intonation. Finnish-side speakers exhibit fewer f0 peaks and slower intonational movement, echoing Finnish language traits. [P1] and [P4] analyze durational patterns in consonant quantity realization in two North Sámi dialects. The Q2-Q1 (long-short) contrast remains consistent, while Q3-Q2 (overlong-long) contrast varies between dialects. The Finnish-North Sámi bilinguals, mostly representing the Eastern dialect of Finnmark North Sámi display clearer durational patterns, while the Norwegian-North Sámi bilinguals potentially signal this contrast through other acoustic features. [P4] focuses on f0, intensity, and durational features linked to the phonetic manifestation of ternary quantity. Results suggest f0-related features notably ...